Evaluasi Penanganan Dokumen Rekam Medis Terkait Penyebaran Infeksi Covid-19 - Naila Zulfa Nadya; Faizah Wardhina; Riko Ijami (HB PRESS, 2023)
Medical recorders can be directly or indirectly infected with the coronavirus, and even the risk will be greater. Medical recorders who handle parts of patient files can be at risk of infection because they are in direct contact with patient files that may have been exposed to the coronavirus, so medical records need to be handled properly. This study aims to evaluate the handling of medical record documents related to the spread of covid-19 infection at the Tk.III Dr. R. Soeharsono Banjarmasin Hospital. This research uses a qualitative approach to descriptive methods, with 4 primary informants (2 nurses for COVID-19 patients and 2 medical record officers) and 2 triangulation informants (the head nurses for COVID-19 patients and the head of the medical record installation). The research instrument used was an observation and interview guide. The results showed that the procedures for maintaining medical records during the treatment period at Tk.III Dr. R. Soeharsono Banjarmasin Hospital have not made regulations in written form including Standard Operating Procedure. The nurse learned that the medical records of Covid-19 patients should be placed in the nurse station and should not be taken to the treatment room to avoid virus contamination. The filling of medical record documents for Covid-19 patients is no different from ordinary patients. Procedures for maintaining medical records of Covid-19 patients who go home or die at Tk.III.Dr.R. Soeharsono Banjarmasin hospital has made rules in the form of Standard Operating Procedure but some procedures cannot be carried out.